Orbital solitary fibrous tumor with multinucleate giant cells: Case report of an unusual finding in an uncommon tumor - Kaustubh Mulay; Santosh G Honavar (Wolters Kluwer Medknow Publications, 2013)
Solitary fibrous tumor (SFT) is a rare soft-tissue neoplasm which may occur at any site although it is more frequent in the pleura, mediastinum and lung. Orbital involvement by SFT is uncommon. Giant cells are extremely rare to be seen in a SFT and have been described to be immunoreactive for CD34. We present a case of orbital SFT with multinucleate giant cells expressing CD68 and lacking immunoreactivity for CD34. The differential diagnosis is discussed.